Contrasting global imagery to local realities in the postcolonial waterfronts of Malaysia’s capital cities - Stevens, Quentin; Kozlowski, Marek; Ujang, Norsidah (Directory of Open Access Journals, 2016)
Urban waterfront redevelopments are often about image-making for economic and political gain. This article analyses three major recent waterfront projects within the Kuala Lumpur metropolitan area: Kuala Lumpur City Centre, the River of Life, and Lake Putrajaya. All have been important in projecting an image of a modern, developed, postcolonial Malaysia. The article examines these waterfront landscapes in relation to three key themes: their contribution to the overall city image, to economic development, and to ecological performance. The article draws upon policy documents, project plans, interviews with local policymakers, designers and academics, field observation of the current physical development, land use and social use of the three waterfront precincts, and a mental mapping survey of users' cognitive images of how these precincts fit within the overall city image. Analysis shows that the appearance, use and development process of these three waterfront projects draw heavily on international models. The article suggests several waterfront sites and uses within the three projects that indicate a more authentic local paradigm for urban waterfront development.